Impact of Luminal \(α\)-Glucosidase Inhibition on Lipogenic and Glycaemic Enzymes in Obese Diabetic Rats: Consequences for the Treatment of Type 2 Diabetes - Orien Lee Tulp (Medical Science: Trends and Innovations Vol. 10, 2025)
The global prevalence of obesity+T2DM is approaching endemic proportions throughout much of Industrializes society, with no easy resolution on the horizon. In these conditions, the activities of certain insulin-linked glycemic and lipogenic enzymes including glucokinase, malic enzyme, and glucose-6-phosphate dehydrogenase typically become elevated, as consistent contributors to the elevations in plasma lipid profiles and relative adiposity that are also typically observed in such individuals. The use of miglitol, an alpha-glucosidase inhibitor, has been shown to cause a dose-related delay in luminal sucrose digestion in the upper regions of the small intestine, and in an attenuated and delayed response in the glycemic excursions that normally follow a carbohydrate meal. This study aims to determine the effect of delayed carbohydrate (sucrose) digestion in type 2 diabetes mellites on the activity of glycemic and lipogenic enzyme parameters. Groups (n=6-8/group, mean BW 264±5g vs 263±4g) of young adult male obese T2DM (diabetic) SHR/Ntul//-cp rats were fed a nutritionally complete USDA-formulated diet containing 54% sucrose (CONTROL) or the same diet with 150 mg of the luminal \(α\)-glucosidase inhibitor miglitol (MIG) for up to 8 weeks. Standardized analytical procedures established in our laboratory were utilized to quantify the findings. All the collected data were analyzed via standard statistical procedures including student t-test, ANOVA, and Pages L test for trend analysis. All animals demonstrated profound (4+) glycosuria by 8 weeks of age to confirm T2 DM. Body Weight Gain (BWG), relative adiposity and glycosuria were elevated in control animals but decreased significantly following miglitol. Measures of oral Glucose Tolerance (OGT, 250 mg glucose/kg BW, via gavage), AUC for glucose and insulin response to OGT and glycated hemoglobin (HbA1c) were elevated in controls and decreased by 20% after miglitol treatment. Hepatic Glucokinase (GK), malic enzyme (ME) and glucose-6-phosphate dehydrogenase (G6PD) were elevated in the Controls and decreased toward normalization following miglitol treatment. In conclusion, these observations indicate that an 8-week course of miglitol is an effective agent in improving the magnitude of the elevated glycemic and lipogenic enzymes and their impact on developing adiposity in the SHR/Ntul//-cp genetic rat strain of obesity+T2DM and may be an effective adjunct in clinical management of obesity, hyperlipidemia and T2DM. In future studies, it would be productive to extend the luminal therapeutic options beyond the post-adolescent life stage of this investigation to more fully determine the long-term potential of the physiological benefits of luminal \(α\)-glucosidase inhibition health and longevity in an animal model predisposed to early onset obesity, insulin resistance and T2DM.